PENERAPAN MODEL PEMBELAJARAN AKTIF THE POWER OF TWO UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DENGAN KOMPETENSI DASAR “MENDISKRIPSIKAN PELAKU – PELAKU EKONOMI” KELAS VIII B SEMESTER I DI MTs BURHANUL A - Lina Sugiarti; Dassucik Dassucik (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
KTSP assesses student learning outcomes in the process of achieving and understanding what is being learned, therefore, students need to know the criteria for mastery of competencies which will be used as a standard for assessing learning outcomes, so that students can prepare themselves through mastery of the following competencies. developed based on specific objectives studied in accordance with the competencies mastered. Classroom Action Research Design (CAR). This research is said to be classroom action research from the beginning to the end of the study. Kurt Lewin's model research method, namely classroom action research described in a spiral consisting of four phases, namely the planning phase (planning); action (action); observation (observation); and reflection (reflection). In the implementation of the observation meeting I cycle I it is known that the category of student activity is 53%, namely inactive. At the second meeting of the first cycle in observing student activity, it is known that 67% or it is said to be active. The results of the analysis of daily tests I can be seen in the appendix. Based on these results, data were obtained from 10 students who did not complete the test from 33 students who took daily tests or 30% classically, because these students scored less than 70% of the maximum score of 100 and 23 students completed individually. Classical mastery of learning reached 70%. In the implementation of the observation meeting I cycle II, it is known that the category of student activity is 84%, namely active. At the second meeting of cycle II in observing student activity it is known that 94% or it is said to be very active. The results of the analysis of daily tests II. Based on these results, the complete data is obtained classically 100%, because these students get a score of more than> 70 from a maximum score of 100 of 23 students complete individually. Student learning outcomes in cycle II have improved quite well if compared to before the action and cycle I and the study was stopped in Cycle II.